Presiding Judge Mario Olmos Keynotes Fresno County Bar Association Luncheon re Court Filings - Watkins, Howard::::::::: (1989)
Friendship Center for the Blind (FCB) Braille Instructor Greg Matthal presenting a Braille version of U.S. Constitution to FCB Executive Director Philip Kimble with Fresno County Bar Association President G. Dana French looking on.